Strengthening of steel I-Section girder web with depth discontinuity against localized buckling (Fracture and Structural Integrity, 2025)
Stepped steel girders and beams with a jump in section depth are highly susceptible to local web buckling at the step location. Although tapered steel girders have been studied extensively by researchers, abruptly stepped steel girders have been very rarely investigated. This study uses the finite element method to investigate the local web buckling of stepped steel I-section girders. Firstly, linear buckling analysis is verified against experimental results and the AISC-360 and Eurocode 3 formulae. Then, a case study of stepped steel girder failure during construction is presented and discussed. Finally, the effect of step height, step location, boundary conditions, and adding stiffeners on the local web buckling of stepped girders was investigated. Stepping the girder section was found to cause local web buckling at significantly low loads, reaching only 27% of the original buckling capacity in some cases. Moving the step from the compression flange to the tension flange, or to lower moment locations in the girder, can mitigate the problem. When the step needs to be in the compression flange at high moment points, using a long enough horizontal stiffener was found to almost fully restore the web buckling capacity, while using a vertical one only restores about half of the original buckling capacity. Using both vertical and horizontal stiffeners almost doubles the buckling capacity at the step.
Keywords: steel; web buckling; finite element analysis; stepped girders